Religiosidad y espiritualidad en Valdeorras - Borro Fernández, Jesús (Madrygal. Revista de Estudios Gallegos, 2025)
In this article we seek to highlight some of the most picturesque pilgrimage festivals in Valdeorras and eastern Ourense, such as that of Nosa Señora das Ermidas, in O Bolo, and O Pai Eterno, held in parishes like Lardeira and Quintela de Umoso, together with the curious rites associated with them, blending religiosity and superstition—both still very much present in the Galician countryside.